Faith-based mental health provision in Africa: a mixed methods systematic review - Nanji, Nadine (Department of Public Health and Family Medicine, 2023)
Faith-based mental health provision as a model of mental health service delivery is not widely acknowledged or researched, despite being highly utilised, especially in the African context. There is currently limited empirical research or review work on the various types of faith-based health providers which contribute mental health services, the magnitude of these services, or their quality. This mixed-methods systematic review study looked at these aspects of faith-based mental health provision in the African context. In the first phase of this study, we conducted a scoping review with a wider, which resulted in a typology of models of faith-based mental health provision The typology included five different types of faith-based health individual and organisational providers (herbalists, traditional and faith healers, Christian and Muslim clergy, faith-based organisations, and chaplains). In the second phase of the study, we conducted a systematic review based on the typology in which we assessed these models of FBHP against service type and level (facility or community, individual or organisational providers); medical provision type (biomedical or alternative). There were 53 studies included in this systematic review and the findings suggest that there is a wide array of types of faith-based providers providing a variety of mental health services across Africa. The research question formulated for the purposes of the systematic review aim to address the types, magnitude and quality of faith-based mental health services in Africa. For the purposes of this review, magnitude was categorised as including frequency of utilisation and availability of faith-based mental health services, but the information was limited. In addition, there are red flags regarding the quality of these mental health services which include human rights abuses that were discussed in this review. This exploratory review demonstrates some of the challenges in dealing with the complex variety of 'religious entities' in Africa. To some degree, developing conclusions that are applicable to all faith-based mental health providing entities is counterproductive - and instead a main conclusion is that future research and engagement needs to take this variety into account. There are a few common trends - for example challenges facing most faith-based providers in relation to faith-based provision of mental health services is financial support for mental health services. Regarding both traditional/alternative and biomedical mental health services, it has been noted that, there is a need to consider cost to the patient (e.g., reduce out of pocket payments). In addition, the literature suggests that better training for some types of faith-based health providers is urgently needed, especially those working close to community. Community mental health education interventions could strengthen faith-based provision of mental healthcare, and prevent some human rights abuses (religious perils), and improve the quality of faith-based mental health service provision. Better referral systems and improved communication between faith-based health providers and biomedical practitioners is required. In addition, varied types of faith-based health providers need to be included in mental health policy development and implementation. Finally, the most comprehensive conclusion of this exploratory review, is that further research is needed on specific types of faith-based providers engaged in mental health service provision, and further research is needed on the integration of mental health services in African health systems.